Ocorrência de larvas de Philornis deceptiva (Dodge & Aitken, 1968) (Diptera: Muscidae) na Maria–branca, Xolmis cinerea (Vieillot, 1816) (Aves: Tyrannidae), no município Seropédica, Rio de Janeiro, Brasil (Lundiana: International Journal of Biodiversity, 2008)
A young of the gray monjita, Xolmis cinerea, sustained 19 larvae of Philornis sp. during its breeding period from September to October, 2006, in the municipality of Seropédica. Larvae were observed since the 3rd day after hatching. They were taken off and put in an artificial nest into plastic box and their life cycle observed until emergence. Fifteen larvae reached the adult stage and were preserved in alcohol 70% for further identification. This is the first record of Xolmis cinerea as a potential host for Philornis.